INFORMATION TRANSFER TECHNIQUE FOR ASSESSING EFL LISTENING: A NARRATIVE REVIEW OF THEORY AND CLASSROOM PRACTICE - Iswandini Agustin (BEGIBUNG: Jurnal Penelitian Multidisiplin, 2026)
Listening assessment should measure learners' ability to understand spoken language in authentic contexts. One alternative technique is Information Transfer, which requires learners to convert spoken information into visual representations such as tables, charts, maps, or diagrams. This narrative literature review examines the theoretical foundations, characteristics, classroom applications, advantages, limitations, and pedagogical implications of Information Transfer in EFL listening assessment. The findings suggest that the technique promotes authentic and learner-centered assessment by emphasizing meaningful listening while reducing the influence of reading and writing skills. However, its effectiveness depends on appropriate task design, suitable listening materials, and learners' proficiency levels. Information Transfer therefore offers a practical alternative to conventional listening assessment in EFL classrooms.